Viability of using energy storage for frequency regulation on power grid. (May 2018) - Lim, Y S; Hau, L C; Loh, K Y; Lim, K Y; Lyons, P F; Taylor, P C
Abstract: This project is about the development and integration of a real-time network simulator in the laboratory using hardware in the loop (HIL) for the purpose of frequency regulation. Frequency regulation is done using the energy storage system (ESS) and a real-time network test bed developed in the smart energy laboratory in Newcastle University. An IEEE Test System was built in the OPAL-RT network simulator to mimic the power grid with renewable energy sources. The study demonstrates the viability of using an ESS to regulate the frequency under an increased penetration of renewable energy sources.